2021
DOI: 10.3892/ijmm.2021.5012
|View full text |Cite
|
Sign up to set email alerts
|

Interference with the expression of S1PR1 or STAT3 attenuates valvular damage due to rheumatic heart disease

Abstract: Rheumatic heart disease (RHd) affects numerous individuals annually; however, its pathogenesis remains unclear. The sphingosine 1-phosphate receptor 1 (S1PR1) and signal transducer and activator of transcription 3 (STAT3) have recently been shown to be involved in valvular damage via the promotion of the differentiation of T helper 17 (Th17) cells during the development of RHd-induced valvular damage. The present study investigated whether altering the expression of S1PR1 or STAT3 attenuates valvular damage du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Previous studies have also reported infiltration of CD4 + lymphocytes into the neovascularization area of RHD valves [47]. Furthermore, our previous studies and those of others have shown a close relationship between valvular damage and Th17 cells that differentiated from CD4 + T cells [15,40,48]. Th17 cells that differentiated from CD4 + T cells are the key factors during the pathogenesis of RHD [49].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous studies have also reported infiltration of CD4 + lymphocytes into the neovascularization area of RHD valves [47]. Furthermore, our previous studies and those of others have shown a close relationship between valvular damage and Th17 cells that differentiated from CD4 + T cells [15,40,48]. Th17 cells that differentiated from CD4 + T cells are the key factors during the pathogenesis of RHD [49].…”
Section: Discussionsupporting
confidence: 65%
“…The classical method was used to establish the RHD rat model [14,[37][38][39][40] over a period of 9 weeks. At the beginning of the experiment, rats in the RHD group were treated with unilateral rear footpad injections of a 1:1 (v/v) mixed solution of 0.1 mL of antigen and CFA.…”
Section: Animals and Groupsmentioning
confidence: 99%
“…In the context of autoimmune diseases, its suppression aligns with protective mechanisms against myocardial injury, particularly through the inhibition of miR‐23 22 . The dynamic interplay between LINC00707, microRNAs and target genes underscores its potential as a therapeutic target in various pathological conditions 23,24 . Although some investigations have shed light on the role of LINC00707 in HCC, 12,13 there remains a substantial gap in our understanding.…”
Section: Discussionmentioning
confidence: 99%
“… 22 The dynamic interplay between LINC00707, microRNAs and target genes underscores its potential as a therapeutic target in various pathological conditions. 23 , 24 Although some investigations have shed light on the role of LINC00707 in HCC, 12 , 13 there remains a substantial gap in our understanding. As a result, this investigation validated the oncogenic role of LINC00707 in HCC through assessments like cell colony assays, transwell migration and transwell invasion assays.…”
Section: Discussionmentioning
confidence: 99%
“…Its conjugate GDCA upregulates ZBP1 in macrophages promoting necroptosis and accelerated fibrosis in a BDL model with relevance for EHBA 64 . Importantly, activation of S1PR by its endogenous ligand sphingosine 1 is linked to STAT3 activation in Tregs, their infiltration into tumor tissue 65 , and Th17/Treg balance in rheumatic heart disease and aplastic anemia 66, 67 .…”
Section: Discussionmentioning
confidence: 99%